Harmony

Calculus Level 5

If

n = 1 H n ( 2 ) n 2 \sum_{n=1}^\infty \frac{H_n^{(2)}}{n^2}

can be expressed in the form a π k b \dfrac{a\pi^k}{b} , where a , b a, b , and k k are positive integers with a a and b b coprime, find a + b + k a+b+k .

Notation : H n ( s ) = m = 1 n 1 m s \displaystyle H_n^{(s)} = \sum_{m=1}^n \frac{1}{m^s} .


The answer is 371.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Mark Hennings
Feb 22, 2016

The sum is n = 1 H n ( 2 ) n 2 = n m 1 1 m 2 n 2 = n > m 1 1 m 2 n 2 + n = 1 1 n 4 = 1 2 m n 1 m 2 n 2 + ζ ( 4 ) = 1 2 [ ( n = 1 1 n 2 ) 2 n = 1 1 n 4 ] + ζ ( 4 ) = 1 2 [ ζ ( 2 ) 2 + ζ ( 4 ) ] = 7 360 π 4 \begin{array}{rcl} \displaystyle \sum_{n=1}^\infty \frac{H_n^{(2)}}{n^2} \; = \; \sum_{n \ge m \ge 1} \frac{1}{m^2n^2} & = & \displaystyle \sum_{n > m \ge 1} \frac{1}{m^2n^2} + \sum_{n=1}^\infty \frac{1}{n^4} \; = \; \tfrac12\sum_{m \neq n} \frac{1}{m^2n^2} + \zeta(4) \\ & = & \displaystyle \frac12\left[\left(\sum_{n=1}^\infty \frac{1}{n^2}\right)^2 - \sum_{n=1}^\infty \frac{1}{n^4}\right] + \zeta(4) \\ & = & \tfrac12\big[\zeta(2)^2 + \zeta(4)\big] \; =\; \tfrac{7}{360}\pi^4 \end{array} making the answer 7 + 360 + 4 = 371 7 + 360 + 4 = \boxed{371} .

As intended.

In fact, by inspection of the product and series expansions of sin x / x \sin x / x , one can derive the identity

ζ ( 2 , 2 , , 2 n ) = π 2 n ( 2 n + 1 ) ! \zeta(\underbrace{2,2,\ldots,2}_n) = \frac{\pi^{2n}}{(2n+1)!}

Jake Lai - 5 years, 3 months ago
Julian Poon
Feb 22, 2016

The sum can be expressed as

n = 1 m = 1 n 1 ( m n ) 2 \sum_{n=1}^{\infty}\sum_{m=1}^{n}\frac{1}{(mn)^2}

Rearranging the terms, we get

n = 1 m = 1 n 1 ( m n ) 2 = n = 1 1 n 2 + n = 2 1 ( 2 n ) 2 + n = 3 1 ( 3 n ) 2 . . . \sum_{n=1}^{\infty}\sum_{m=1}^{n}\frac{1}{(mn)^2}=\sum_{n=1}^{\infty}\frac{1}{n^2}+\sum_{n=2}^{\infty}\frac{1}{(2n)^2}+\sum_{n=3}^{\infty}\frac{1}{(3n)^2}...

= k = 1 1 k 2 n = k 1 n 2 = k = 1 1 k 2 ( ζ ( 2 ) n = 1 k 1 1 k 2 ) =\sum_{k=1}^{\infty}\frac{1}{k^2}\sum_{n=k}^{\infty}\frac{1}{n^2}=\sum_{k=1}^{\infty}\frac{1}{k^2}\left(\zeta(2)-\sum_{n=1}^{k-1}\frac{1}{k^2}\right)

= ζ ( 2 ) 2 n = 1 H n 1 ( 2 ) n 2 =\zeta(2)^2-\sum_{n=1}^{\infty}\frac{H^{(2)}_{n-1}}{n^2}

Since H n 1 ( 2 ) = H n ( 2 ) 1 n 2 H^{(2)}_{n-1}=H^{(2)}_{n}-\frac{1}{n^2}

n = 1 H n 1 ( 2 ) n 2 = n = 1 H n ( 2 ) n 2 1 n 4 = n = 1 H n ( 2 ) n 2 ζ ( 4 ) \sum_{n=1}^{\infty}\frac{H^{(2)}_{n-1}}{n^2}=\sum_{n=1}^{\infty}\frac{H^{(2)}_{n}}{n^2}-\frac{1}{n^4}=\sum_{n=1}^{\infty}\frac{H^{(2)}_{n}}{n^2}-\zeta(4)

Putting it all together

n = 1 m = 1 n 1 ( m n ) 2 = ζ ( 2 ) 2 n = 1 H n ( 2 ) n 2 + ζ ( 4 ) \sum_{n=1}^{\infty}\sum_{m=1}^{n}\frac{1}{(mn)^2}=\zeta(2)^2-\sum_{n=1}^{\infty}\frac{H^{(2)}_{n}}{n^2}+\zeta(4)

n = 1 H n ( 2 ) n 2 = ζ ( 2 ) 2 n = 1 H n ( 2 ) n 2 + ζ ( 4 ) \sum_{n=1}^{\infty}\frac{H^{(2)}_{n}}{n^2}=\zeta(2)^2-\sum_{n=1}^{\infty}\frac{H^{(2)}_{n}}{n^2}+\zeta(4)

n = 1 H n ( 2 ) n 2 = 1 2 ( ζ ( 2 ) 2 + ζ ( 4 ) ) \sum_{n=1}^{\infty}\frac{H^{(2)}_{n}}{n^2}=\frac{1}{2}\left(\zeta(2)^2+\zeta(4)\right)

Substituting ζ ( 2 ) = π 2 6 \zeta(2)=\frac{\pi^2}{6} and ζ ( 4 ) = π 4 90 \zeta(4)=\frac{\pi^4}{90} , we get

n = 1 H n ( 2 ) n 2 = 7 π 4 360 \sum_{n=1}^{\infty}\frac{H^{(2)}_{n}}{n^2}=\boxed{\frac{7\pi^4}{360}}

Moderator note:

Good explanation.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...